Analisis Peningkatan Kinerja Pegawai dan Kemampuan Pengelolaan Arsip - Ismiyati Ismiyati (JSSH (Jurnal Sains Sosial dan Humaniora), 2020)
Village governance has the broadest scope of autonomy that is as point center in implementing government programs. Consequently, the governance should prepare to improve the performance of their employee and archive management, so that it runs effectively and efficiently in providing the services for society. The hypothesis in this study is whether is an influence of physical work environment, work facilities, employee competence on the archives management and performance employees. Methods and data collection use interviews, documentation, and questionnaires. Data analysis uses Structural Equation Modeling (SEM) by using LISREL version 8.51. Results of study measurements obtained equation of regression PA = 0.57 + 0, 37LKF + 0, 37FASKER + 0, 25KOMPEG, Errorvar = 0.0036, R2 = 1.00 and KINPEG = 0, 21LKF + 0, 16FASKER + 0, 63KOMPEG, Errorvar = 0.00, R2 = 1.00. The results showed that the physical work environment, work facilities, and employee competence positively influenced the archive management and performance employees.